DEVELOPMENT OF COORDINATION SKILLS IN SENIOR AND PREPARATORY GROUP CHILDREN IN THE PROCESS OF PEDAGOGICAL EXPERIMENT - Barno Pulatovna Abdullaeva (American Journals, 2023)
The article presents the results of research work on teaching football elements in pre-school instituitons. Moreover, the results are compared gender-based: girls and boys in senior and preparatory groups of pre-school-institutions.
Keywords: movement skills, development of children, technical football elements, pre-school students, pre-school preparatory groups, senior groups.